Transformation of 3-(Furan-2-yl)-1,3-di(het)arylpropan-1-ones to Prop-2-en-1-ones via Oxidative Furan Dearomatization/2-Ene-1,4,7-triones Cyclization - Roman O. Shcherbakov (Molecules, 2021)
The approach to 3-(furan-2-yl)-1,3-di(het)arylprop-2-en-1-ones based on the oxidative dearomatization of 3-(furan-2-yl)-1,3-di(het)arylpropan-1-ones followed by an unusual cyclization of the formed di(het)aryl-substituted 2-ene-1,4,7-triones has been developed. The cyclization step is related to the Paal–Knorr synthesis, but the furan ring formation is accompanied in this case by a formal shift of the double bond through the formation of a fully conjugated 4,7-hydroxy-2,4,6-trien-1-one system or its surrogate.